Using Tissue Culture Technique for the Production of Cardiac Glycosides From Roots of Digitalis purpurea L Plantlets - Zeinab J. Aawad; Ekbal H. Al- Khateeb (College of Pharmacy University of Baghdad, 2017)
The present study was performed using the tissue culture technique , where by roots formation was stimulated shoot tips of Digitalis  purpurea L plant using auxins in this study ,shoot tips (1cm length ) were excised from sterilized seedlings of Digitalis purpurea L.Var Excelsior mixed , then they were cultured on MS medium with the addition of one of the auxins IAA, IBA  ,NAA of different concentration ( 0.0 ,0.05 ,0.1 ,0.5 and 1.0 mg / L ).  After 45 days of starting the culture results showed that the treatment 0.5 mg/ L of IBA had a high significant effect on the dry weight of roots formation and containing Digitoxin and Gitoxin whose quantities as a rate of ( 2.96 gm , 30.01 and 11.05 mg/gm dry weight respectively .Also this treatment has given highest values with the other studied characteristics where the percent of the soluble sugars and starch and they are ( 2.48 % , 2.82%) respectively  Abbreviation  (Indole Butyric Acid )IBA , ( Indole Acetic Acid )IAA ,  ( Murashige and skoog medium , 1962 )  MS ,  (Naphthalen acetic Acetic )  NAA  , ( Milligram ) Mg , ( Microgram )ug , (Litter ) L , (Gram) gm .